Engineering Mechanics of Solids - Popov (Egor P); Balan (Toader A) (2004)
Solid Mechanics
39693a.jpg;39693b.jpg;39693c.jpg;39693d.jpg;39693e.jpg;39693f.jpg;39693g.jpg;39693h.jpg;39693i.jpg;39693j.jpg
22.5
Keywords: Solid Mechanics